Temporal dynamics of offline transcranial ultrasound stimulation - Cyril Atkinson-Clement; David Howett; Mohammad Alkhawashki; James Ross; Ben Slater; Marilyn Gatica; Fabien Balezeau; Chencheng Zhang; Jerome Sallet; Chris Petkov; Marcus Kaiser (Current Research in Neurobiology)
Transcranial ultrasound stimulation (TUS) is a promising non-invasive neuromodulation modality, characterized by deep-brain accuracy and the capability to induce longer-lasting effects. However, most TUS datasets are underpowered, hampering efforts to identify TUS longevity and temporal dynamics. This primate case was studied awake with over 50 fMRI datasets, with and without left anterior hippocampus TUS. We therefore amassed the highest-powered TUS dataset to date required to reveal TUS longevity and dynamics. Most of the effects were found in the TUS region itself and alongside the default mode and sensorimotor networks. Seed-based functional connectivity exhibited a time-constrained alteration which dissipated ∼60 min post-TUS. Intrinsic activity measure and regional homogeneity displayed extended diffusivity and longer durations. This high-powered dataset allowed predicting TUS using pre-stimulation features that can now extend to modeling of individuals scanned less extensively. This case report reveals the diversity of TUS temporal dynamics to help to advance long-lasting human applications.